2017
DOI: 10.1111/jam.13552
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae community shifts during the biogas upgrading in an alkaline open photobioreactor

Abstract: The alkaline conditions enhance the CO absorption from biogas and could optimize specialized microalgae communities in the open photobioreactor. Denaturing gradient gel electrophoresis fingerprinting and richness index comparison are useful methods for the evaluation of microalgae community shifts and photosynthetic activity performance, particularly in systems intended for CO removal from biogas where the CO assimilation potential can be related to the microbial richness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 44 publications
0
5
1
Order By: Relevance
“…S3). It has been previously reported that algal biomass activity is proportional to the pond temperature up to an optimum, above which, increasing algal respiration and photorespiration reduces the overall biomass productivity [11,20]. However, no significant difference at p < 0.05 between the average temperatures recorded from April to October was observed in this study (Table 1, mmc: Fig.…”
Section: Environmental Parameterscontrasting
confidence: 53%
See 2 more Smart Citations
“…S3). It has been previously reported that algal biomass activity is proportional to the pond temperature up to an optimum, above which, increasing algal respiration and photorespiration reduces the overall biomass productivity [11,20]. However, no significant difference at p < 0.05 between the average temperatures recorded from April to October was observed in this study (Table 1, mmc: Fig.…”
Section: Environmental Parameterscontrasting
confidence: 53%
“…Thus, the slight pH seasonal variations did not have a statistically significant effect on the algal and prokaryotic community (p < 0.15 and p < 0.75, respectively). The algal community was mainly composed of freshwater chlorophyte genera that can tolerate pH values up to 10.6-11, such as Chlorella, Scenedesmus and Desmodesmus [11]. However, the impact of the other environmental conditions on the metabolism of microalgae resulted in C. vulgaris as the dominant species in the HRAP.…”
Section: Impact Of the Interaction Algae-prokaryotes And The Seasonal Variation On The Main Biological Communities Found During Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…and Pseudanabaena sp. reported by Granada-Moreno et al (2017) was used for all the experiments. AMC was grown in mineral salt medium (MSM) containing (g/L) Na 2 CO 3 (4.03), NaHCO 3 (13.61), NaCl (1), K 2 HPO 4 (1), K 2 SO 4 (1), CaCl 2 Á2H 2 0 (0.4), KNO 3 (2.53) and MgCl 2 Á6H 2 O (0.203) according to de los de los Cobos-Vasconcelos et al (2016), and 2 mL/L of micronutrient solution as reported by Sorokin et al (2001).…”
Section: Microorganisms and Culture Conditionsmentioning
confidence: 99%
“…At this point, it is worth to highlight that during the upgrading of gas streams using microalgal-bacterial cultures, all microorganisms involved are subjected to dynamic changes depending on the operational conditions, the time of exposure to gas contaminants and nutrients supply [15]. Therefore, the ad-hoc control of microalgae biomass composition during the photosynthetic biogas upgrading can enhance the economic sustainability of the process by producing a biomass feedstock with a tailored valorization potential.…”
Section: Introductionmentioning
confidence: 99%